The Effect of Modified Tai Chi Exercises on the Physical Function and Quality of Life in Elderly Women With Knee Osteoarthritis - Song, Jiulong; Wei, Lijun; Cheng, Kai; Lin, Qiang; Xia, Peng; Wang, Xinwei; Wang, Xiaoju; Yang, Ting; Chen, Baoyi; Ding, Aimei; Sun, Mingyi; Chen, Anliang; et al. (Frontiers in Aging Neuroscience, 2022)
Background: Knee osteoarthritis (KOA) is the leading cause of pain and stiffness, affecting older adults' physical function and quality of life. As a form of mind-body exercise, Tai Chi has been recommended as an exercise prescription for KOA patients. This study examined the effects and continuation of modified Tai Chi exercises on physical function and quality of life in the elderly women with KOA. Methods: We conducted a single-blind, randomized controlled trial (RCT) on 40 older women with KOA. The participants were randomized to a 12 weeks Tai Chi or control group. The Tai Chi group attended a kind of modified Tai Chi training sessions three times per week; the control group attended wellness education sessions once a week. The primary outcome was the Western Ontario and McMaster University Osteoarthritis Index (WOMAC). Secondary outcomes were Berg Balance Scale (BBS), Timed Up and Go (TUG), Short-Form 36 (SF-36), Pittsburgh Sleep Quality of Index (PSQI), Self-rating Anxiety Scale (SAS), and Self-rating Depression Scale (SDS). Results: After the 12-weeks the Tai Chi group significantly improvement in the WOMAC pain (mean difference, -5.09 points, p= 0.001), WOMAC stiffness (mean difference, -3.60 points, p=0.002), WOMAC physical function (mean difference, -11.21 points, p=0.001) compared to the control group. In addition, the Tai Chi group had also significant improvement in the BBS (mean difference, 1.70 points, p=0.008), TUG (mean difference, -0.52s, p=0.001), SF-36PCS (mean difference, 7.60 points, p=0.001), MCS (mean difference, 7.30 points, p=0.001), PSQI (mean difference, -3.71 points, p=0.001), SDS (mean difference, -5.37 points, p=0.025) and SAS (mean difference, -5.06 points, p=0.002). Conclusion: The modified Tai Chi exercises is an effective treatment improved physical function and quality of life in elderly women with KOA.